Processamento de coloidal de α-Al₂O₃ e a seletividade superficial na adsorção específica de taninos. - Webber, Jaíne (My University, 2018)
Surfaces interactions dominate the properties of colloidal particles suspension. The balance between surface, solvent, and active species in solution determines the properties related to the solid-liquid interface interactions and reactivity. Tannin is a natural compound extracted from acacia bark, which can be used as a stabilizing and dispersing agent in alumina colloidal ceramic suspensions. The control of alumina surface properties and the mechanisms that rules its interactions with alumina is fundamental to adjust its effects on colloidal processing. It becomes necessary to ensure a contaminant-free surface to evaluate the contribution and effect of each suspended species. In this work, it has been investigated the adsorption of hydrolysable (TH), condensed (TC) and sulfonated (TS) tannins on dialyzed α-Al2O3 particles (AD). The correlation between the obtained results for the characterization of α-Al2O3 indicates that surface sites like AlVI-μ¹-OH, AlVI-μ²-OH and AlVI-μ³-OH coexists, and in addition, an extra AlIV-μ¹-OH site must be taken into account. The degree of protonation of such sites is controlled by the conditions of the medium, essentially by pH, displaying that the α-Al2O3 particles surface is heterogeneous. The net contribution of the suspended tannins was mainly defined by the pH of the medium, since this solvent property also defined the state of protonation and deprotonation of the polar groups in the molecules. The maximum adsorption of TH and TC on α-Al2O3 (9.72 m²/g) was 12.47 and 14.60 mg/g, respectively. The TS acquires a high negative electric charge and this, in turn, limits the adsorbed amount to 7.34 mg/g, mainly due to the electrical barrier that is formed by its adsorption. This electrostatic barrier provides stability of up to -65 mV to the suspensions when the surface is fully covered, imparting robust dispersion to the particles (dH=300 nm), which is not affected by the increase in the ionic strength of the medium. The initial stability of the α-Al2O3 suspensions (+60 mV) was progressively reduced both with increasing adsorption of TH and TC as well as ionic strength of the medium; for suspensions with zeta potential between -25 mV and +25 mV, agglomerates from 400 to 700 nm are formed. The adsorption of TH, TC and TS takes place mainly by hydrogen bond between tannin’s phenolic groups and AlVI-μ²-OH on α-Al2O3 by specific adsorption. Under conditions in which the TS partially covers the α-Al2O3 surface, it is suggested that the adsorption takes place only by electrostatic interactions between SO3H groups and positive sites on α-Al2O3, i.e. by non-specific adsorption.
As interações superficiais dominam as propriedades de suspensões de partículas coloidais. O equilíbrio entre a superfície, o solvente e as espécies ativas em solução determina as propriedades relacionadas à reatividade e às interações na interface sólido-líquido. O tanino é um composto extraído da casca de acácia e que pode ser utilizado como estabilizante e dispersante em suspensões cerâmicas coloidais de alumina. O controle das propriedades superficiais da alumina e dos mecanismos que governam sua interação com o tanino é fundamental para ajustar seus efeitos no processamento coloidal. Torna-se necessário garantir uma superfície isenta de contaminantes para avaliar o efeito e a contribuição de cada um dos materiais em suspensão. Neste trabalho foi investigada a adsorção de tanino hidrolisável (TH), condensado (TC) e sulfonado (TS) em partículas de α-Al2O3 dialisadas. A correlação entre os resultados obtidos na caracterização da α-Al2O3 indica que coexistem sítios superficiais AlVI-μ¹-OH, AlVI-μ²-OH e AlVI-μ³-OH; adicionalmente, um sítio AlIV-μ¹-OH deve ser considerado. O estado de protonação de cada sítio é controlado pelas condições do meio, essencialmente pelo pH, revelando que a superfície das partículas de α-Al2O3 é heterogênea. A contribuição dos taninos em suspensão foi definida principalmente pelo pH do meio, uma vez que esta propriedade define o estado de protonação dos grupos polares nas moléculas. A adsorção máxima de TH e TC em α-Al2O3 (9,72 m²/g) foi 12,47 e 14,60 mg/g, respectivamente. O TS adquire uma elevada carga elétrica negativa, o que limita a quantidade adsorvida a 7,34 mg/g, principalmente devido à barreira eletrostática que é formada pela sua adsorção. Essa barreira eletrostática proporciona estabilidade de até -65 mV às suspensões quando a superfície está completamente recoberta, conferindo dispersão robusta às partículas (dH=300 nm), a qual não é afetada pelo aumento da força iônica do meio. A estabilidade inicial das suspensões de α-Al2O3 (+60 mV) foi reduzida progressivamente tanto com o aumento da adsorção de TH e TC quanto da força iônica do meio; para suspensões com potencial zeta entre -25 mV e +25 mV, aglomerados de 400 a 700 nm foram formados. A adsorção de TH, TC e TS ocorre predominantemente por ligações de hidrogênio entre os grupos fenólicos nos taninos e os sítios AlVI-μ²-OH na α-Al2O3, i.e., por adsorção específica. Para condições onde o TS recobre parcialmente a superfície da α-Al2O3, é sugerido que a adsorção ocorra por interações eletrostáticas entre os grupos SO3H e os sítios positivos da α-Al2O3, i.e., por adsorção não específica.
Keywords: Óxido de alumínio; Taninos; Adsorção; Aluminum oxide; Tannins; Adsorption